The opening index in patients with closed lock and with myogenous disorders of the temporomandibular joint. - Karic, Vesna V. (My University, 2014)
Disorders of the temporomandibular joint (TMD) are the most common chronic pain conditions in the dental population. Limitation of mandibular movement is one of the signs of TMD. In this study, a new opening index was examined in patients with myogenous and closed lock TMD disorders. This opening index was determined as a ratio between active and passive opening (Miller et al. In press). Patients were examined for TMD using the procedure of Bezuur et al. (1988) and Hansson (1988). Forty two patients with a TMD of myogenous origin, 11 with a closed lock, and 51 patients with no sign or symptoms of TMD were recruited to the study. ANOVA showed that the opening index of the group of patients with a TMD of .myogenous origin differed from that of a group with closed lock (pO.OOOl), ANCOVA showed that the opening index in ail groups was not dependent on age (p<0.225) or gender (p< 0.569).